Mobile web and intelligent information systems : 14th International Conference, MobiWIS 2017, Prague, Czech Republic, August 21-23, 2017, proceedings /: 14th International Conference, MobiWIS 2017, Prague, Czech Republic, August 21-23, 2017, proceedings. (2017) - Unknown
No abstract available